Endobolome, a New Concept for Determining the Influence of Microbiota Disrupting Chemicals (MDC) in Relation to Specific Endocrine Pathogenesis - Aguilera, Margarita; Gálvez-Ontiveros, Yolanda; Rivas, Ana (Frontiers in Microbiology, 2020)
Endogenous steroid hormones and Endocrine Disrupting Chemicals (EDC) interact with gut microbiota through different pathways. We suggest the use of the term “endobolome” when referring to the group of gut microbiota genes and pathways involved in the metabolism of steroid hormones and EDC. States of dysbiosis and reduced diversity of the gut microbiota may impact and modify the endobolome resulting at long-term in the development of certain pathophysiological conditions. The endobolome might play a central role in the gut microbiota as seen by the amount of potentially endobolome-mediated diseases and thereby it can be considered an useful diagnostic tool and therapeutic target for future functional research strategies that envisage the use of next generation of probiotics. In addition, we propose that EDC and other xenobiotics that alter the gut microbial composition and its metabolic capacities should be categorized into a subgroup termed “microbiota disrupting chemicals” (MDC). This will help to distinguish the role of contaminants from other microbiota natural modifiers such as those contained or released from diet, environment, physical activity and stress. These MDC might have the ability to promote specific changes in the microbiota that can ultimately result in common intestinal and chronic or long-term systemic diseases in the host. The risk of developing certain disorders associated with gut microbiota changes should be established by determining both the effects of the MDC on gut microbiota and the impact of microbiota changes on chemicals metabolism and host susceptibility. In any case, further animal controlled experiments, clinical trials and large epidemiological studies are required in order to establish the concatenated impact of the MDC-microbiota-host health axis.